2017
DOI: 10.1089/lap.2016.0390
|View full text |Cite
|
Sign up to set email alerts
|

Da Vinci Robotic Surgery in a Pediatric Hospital

Abstract: This initial experience confirms that RS is as safe and effective as conventional MAS. A number of selected procedures performed with RS would only benefit from this approach, as it is not suitable for conventional MAS. Although economically demanding, in particular for a pediatric hospital, we firmly believe that centralization of care would allow pediatric surgeons adopting RS to perform complex reconstructive surgical procedures with great advantages for the patients and a minimal increase in overall costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The general surgical applications have been quite varied in adults, but the technique has been particularly useful in urology for prostate surgery (14). There have been few reports that have been published for robotic general pediatric surgery (514). Thus, far, the largest number of procedures and publications have been produced for robotic urological pediatric surgery (1534).…”
Section: Introductionmentioning
confidence: 99%
“…The general surgical applications have been quite varied in adults, but the technique has been particularly useful in urology for prostate surgery (14). There have been few reports that have been published for robotic general pediatric surgery (514). Thus, far, the largest number of procedures and publications have been produced for robotic urological pediatric surgery (1534).…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral [15][16][17][18][19] with encouraging results. The first applications of RAL for pediatric renal tumors were reported by Cost et al, who described in 2012 transperitoneal partial nephrectomy 20 and in 2014 a nephrectomy in an adolescent with WT.…”
Section: Indications Contraindicationsmentioning
confidence: 97%
“…The lack of haptic feedback may be considered as a potential limitation, especially in tumors that cannot be fragmented such as WT. A few case series had been reported since the first article of Meehan et al in 2013 with encouraging results. The first applications of RAL for pediatric renal tumors were reported by Cost et al, who described in 2012 transperitoneal partial nephrectomy and in 2014 a nephrectomy in an adolescent with WT .…”
Section: Introductionmentioning
confidence: 98%
“…There have been few reports that have been published for robotic general pediatric surgery [44][45][46][47][48][49][50][51][52][53]. Numerous case reports, case series, and comparative studies have unequivocally demonstrated that robotic surgery in children is safe [54].…”
Section: Introductionmentioning
confidence: 99%